Molecular characterization of Haemoproteus sacharovi (Haemosporida, Haemoproteidae), a common parasite of columbiform birds, with remarks on classification of haemoproteids of doves and pigeons - Križanauskienė, Asta; Iezhova, Tatjana A.; Sehgal, Ravinder N. M.; Carlson, Jenny S.; Palinauskas, Vaidas; Bensch, Staffan; Valkiūnas, Gediminas (Zootaxa, 2013)
Haemoproteus (Haemosporida, Haemoproteidae) is the largest genus of avian haemosporidian parasites, some species of which cause lethal diseases in birds. Subgenera Parahaemoproteus and Haemoproteus are usually accepted in this genus; these parasites are transmitted by biting midges (Ceratopogonidae) and hippoboscid flies (Hippoboscidae), respectively. As of yet, species of Parahaemoproteus have not been reported to infect doves and pigeons (Columbiformes), parasites of these birds have not been reported to be transmitted by biting midges (Ceratopogonidae). Applying microscopy and PCR based methods, we identified mitochondrial cytochrome b (cyt b) sequences of Haemoproteus sacharovi, a wide-spread parasite of doves and pigeons. Phylogenetic relationships of dove haemoproteids, which traditionally have been classified in the subgenus Haemoproteus, showed that H. sacharovi and H. turtur, common parasites of doves, branch in the clade with Parahaemoproteus species, indicating that these haemoproteids may belong to this subgenus and are likely transmitted by biting midges. This study provides barcodes for H. sacharovi, clarifies the taxonomic positions of H. sa-charovi and H. turtur, and indicates directions for development of classification of avian haemoproteid species. Our anal-ysis shows that the current subgeneric classification of avian haemoproteids is generally effective, but the position of some species may need to be revised.